A new species of spider belonging to the Pardosa lugubris-group (Araneae: Lycosidae) from Far East Asia - Nadolny, Anton A.; Omelko, Mikhail M.; Marusik, Yuri M.; Blagoev, Gergin (Zootaxa, 2016)
A new species, Pardosa koponeni sp. n., is described. The new species is widely distributed in Far East Asia. It was previously confused with P. lugubris (Walckenaer, 1802). The two species have very similar copulatory organs but differ in the colouration of legs II–IV in males and the carapace/femur I ratio in both sexes. The distribution of the new species is mapped using material examined and literature data. To provide a more complete understanding of the boundaries between such closely related species, morphological and DNA barcoding approaches for species discrimination were integrated. Two species of the Pardosa lugubris-group (P. lugubris and P. alacris) were found to share haplotypes, suggesting evidence of hybridization or incomplete lineage sorting, or they are perhaps separate morphotypes of the same species. This is another example of complexity and the value of comparing morphology and DNA barcode data among spiders.